2014
DOI: 10.1590/s1413-70542014000500007
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity, anthocyanins and organic acids content of grape juices produced in Southwest of Minas Gerais, Brazil

Abstract: Phenolic compounds and anthocyanins content in grape juices varies in the cultivar, ripening and climate characteristics. The objective of this work was to characterize and evaluate antioxidant activity of grape juices produced in southwestern Minas Gerais. Grapes were harvested, sanitized and the juices from cultivars 'Bordô', 'Isabel Precoce', 'BRS Violeta' and 'BRS Rúbea' were produced in artisanal equipment by steam extraction and stored for 120 days. The following analyzes were performed during storage: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
3
0
3
Order By: Relevance
“…Apart from their bright and attractive colors, their solubility was also quite high in water. 12,13 The texture of F1 looked drier than that of F2, F3, and F4 because F1 did not have an antioxidant that functioned as a moisturizer. In addition, there was no aroma caused by F1 because there was no active ingredient in Hibiscus flower extract, while F2, F3, and F4 had a distinctively strong Hibiscus flower aroma.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from their bright and attractive colors, their solubility was also quite high in water. 12,13 The texture of F1 looked drier than that of F2, F3, and F4 because F1 did not have an antioxidant that functioned as a moisturizer. In addition, there was no aroma caused by F1 because there was no active ingredient in Hibiscus flower extract, while F2, F3, and F4 had a distinctively strong Hibiscus flower aroma.…”
Section: Resultsmentioning
confidence: 99%
“…A study found that moderate exposition to radiation and temperature increases the accumulation of anthocyanins [53]. Many studies have shown the impact of different climates in anthocyanins accumulation [1,47,54] and organic acids accumulation [55][56][57]. In a study performed in Alentejo, it was found that despite total anthocyanin content have increased during maturation in both years a much warmer and dryer year (with less pluviosity) had a positive impact on the synthesis and accumulation of anthocyanins [1].…”
Section: The Impact Of Temperaturementioning
confidence: 99%
“…Studies have shown an inverse relationship between agerelated diseases and fruit and vegetable consumption due to antioxidants and especially phenolics in fruits and vegetables (Boas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%